2017
DOI: 10.4172/2254-609x.100075
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor Cell Dysfunction: The Role of Endothelial Precursors in Heart Failure

Abstract: Heart failure (HF) a leading cause of premature death in patients with established cardiovascular (CV) disease. Although the global burden of HF is increasing, there is no evidence regarding promising results that improves longterm clinical outcomes especially for HF with preserved and mid-regional pump function. In this context, determination of the vulnerable populations at higher risk of HF development and progression is very promising. Endothelial dysfunction (ED) plays a central role in the manifestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, there is suggested that EPC dysfunction is not only result in etiology effect and co-morbidity influence, but it is independent predictor of HF advance and probably HF-related outcomes. Indeed, previously reported results of other studies provided by wide circle of investigators have shown that the EPCs can appear prior to asymptomatic HF and cooperate with numerous CV risk factors [9,10]. Therefore, EPC dysfunction reflects lowered ability of EPCs in survival, migration and differentiation and thereby it is confirmation a pivotal role of endogenous endothelial repair system in shaping maladaptive cardiac and vascular remodeling and HF development [11,12].…”
Section: %)mentioning
confidence: 96%
“…Moreover, there is suggested that EPC dysfunction is not only result in etiology effect and co-morbidity influence, but it is independent predictor of HF advance and probably HF-related outcomes. Indeed, previously reported results of other studies provided by wide circle of investigators have shown that the EPCs can appear prior to asymptomatic HF and cooperate with numerous CV risk factors [9,10]. Therefore, EPC dysfunction reflects lowered ability of EPCs in survival, migration and differentiation and thereby it is confirmation a pivotal role of endogenous endothelial repair system in shaping maladaptive cardiac and vascular remodeling and HF development [11,12].…”
Section: %)mentioning
confidence: 96%